Towards an Asian theology - Hwa, Yung (Regnum practitioner series., 2020)
"This is a condensed version of the author's seminal work, Mangoes or Bananas? Based on the premise that theology and mission are inseparable, the author applies four missiological criteria to representative examples of Protestant Asian writings to assess their adequacy or otherwise as contextual theologies. The greatest problem with most of these theologies appears to be that, at heart, they have been domesticated by western dualism and Enlightenment thought. Authentic Christian theologies will only emerge with the dual recovery of confidence in both gospel and culture within Asian Christianity"--From the publisher.